KRITIK SOSIAL PADA CERPEN HARIAN SINGGALANG TAHUN 2020 - Siska Novelia (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to describe forms of social criticism about the problem of family disorganization, the problem of crime, the problems of the younger generation in modern society, religious and belief issues, and political and bureaucratic problems. This type of research is qualitative research with descriptive methods. The approach used in this study is the mimesis approach. This research data is singgalang daily short stories in 2020. This data collection technique, namely reading and understanding the short story Singgalang Daily in 2020, recording the words and sentences of the narrator or speech of figures related to social criticism contained in the short story Singgalang Daily in 2020, and identifying data based on social problems that become the expression of social criticism in the short story Singgalang Daily in 2020. Data analysis techniques of this research, namely classifying data according to the theory used, analyzing and interpreting data, concluding research results, and making reports.